(untitled) (Abhat Journal, 2023)
The purpose of this study is to report the results of a small-scale survey study of Libyan medical scholars, set out to determine Libyan academics’ experiences of publishing their research papers. In short, the current study is aimed to identify Libyan medical researchers’ perspectives on using English and/or Arabic in writing medical research papers. It examines at the issue of language choice, the perceived advantages and difficulties being experienced as a result of selecting one or the other language. The findings of the study reveal that all the participants selected English language for writing their research papers. This helps in gaining international recognition for their works, and more readership. Moreover, their study background in English makes it easier for them to read in English than Arabic. The implications of the study are discussed and presented.